PENINGKATAN EFISIENSI BAHAN STRUKTUR BETON BERTULANG DENGAN PENGGUNAAN VARIASI CAMPURAN MUTU BETON PADA DAERAH TARIK BETON - Sukoyo, Sukoyo (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2013)
In a cross-sectional design of reinforced concrete, is generally assumed to be only 30 to 50% higher cross section work withstand being hit withstand tensile rest. From these assumptions and with the use of the model diagram, meaning there are still opportunities to optimize the function of the concrete with the use of lower levels of the cement mixture. With this method the benefits expected to be obtained and optimally efficient use of cement as an adhesive in the construction of reinforced concrete. Experiments carried out by varying the mix proportion of concrete as high as 50% higher for the cross-sectional area that will receive the attractive force. Of the six variations resulting mixture is made that the flexural strength of concrete as indicated by the flexural strength test results obtained that the bending moment variation cement mix with lower levels do not affect the flexural strength of about 9.2 KNm.